Obraz Tartessos w historiografii hiszpańskiej - Krueger, Michał (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
Tartessos, the land mentioned by Greek and Roman written sources and located in western Andalusia, is commonly seen as a legendary, unimaginably rich kingdom. The aim of this paper is to present the role of the historical context on the character of various interpretations of Tartessos, and also to provide the Polish readers with the history of research on this archeologically interesting region. Archival historical and archaeological papers as well as critical historiographic literature on Tartessos have been analysed in the paper. The article also attempts to demonstrate that the image of Tartessos, as shaped through the ages, has been contingent on social and cultural context, as well as more or less deliberate implementation of theoretical concepts.
Images of Tartessos in Spanish historiography